CFD-simulation of three-dimensional dynamic stall on a rotor with cyclic pitch control - Letzgus, J.; Keßler, M.; Krämer, E. (My University, 2015)
Computational fluid dynamics (CFD) simulations of a two-bladed Mach-scaled rotor (R = 0.65 m, Matip = 0.6, Retip _ 1 × 106) with 1/rev cyclic pitch control encountering three-dimensional dynamic stall are presented. The block-structured flow solver FLOWer is used along with the Menter SST turbulence model and a fifth-order spatial CRWENO scheme. A grid and time step dependency study shows the need of high resolution in space and time to properly resolve all stages of dynamic stall. The onset of flow separation in the outboard region of the rotor blade during its upstroke is found to be shock-induced. Flow pattern visualizations reveal the following evolution of a discrete -shaped vortex. Quickly thereafter a partially spanwise vortex occurs, which is bent towards the leading edge near the mid-span. An interaction with the blade tip vortex is noticed as a limitation of outboard-faced separation spreading. Only a small range of outboard radial sections could be found at which the flow pattern resembles two-dimensional dynamic stall. The superposition of an axial flow weakens the dynamic stall event and slightly changes the vortex pattern.
Keywords: Aerodynamics